2016
DOI: 10.1038/srep26223
|View full text |Cite
|
Sign up to set email alerts
|

Network-assisted investigation of virulence and antibiotic-resistance systems in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative bacterium of clinical significance. Although the genome of PAO1, a prototype strain of P. aeruginosa, has been extensively studied, approximately one-third of the functional genome remains unknown. With the emergence of antibiotic-resistant strains of P. aeruginosa, there is an urgent need to develop novel antibiotic and anti-virulence strategies, which may be facilitated by an approach that explores P. aeruginosa gene function in systems-level models. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…None of these proved significant however, which prompted the investigation of potential interactions between resistance genes and virulence genes facilitating gene transfer events. Co-occurrence of virulence genes and antibiotic resistance has been shown in Pseudomonas aeruginosa [52] and has a stronger association than antibiotic use alone in populations of E. coli [53,54]. In the current study, this relationship between antibiotic resistance genes and virulence factors produced the only statistically significant result, with Shannon diversities of these gene categories being positively correlated (0.553, P = 0.05).…”
Section: Resultsmentioning
confidence: 46%
“…None of these proved significant however, which prompted the investigation of potential interactions between resistance genes and virulence genes facilitating gene transfer events. Co-occurrence of virulence genes and antibiotic resistance has been shown in Pseudomonas aeruginosa [52] and has a stronger association than antibiotic use alone in populations of E. coli [53,54]. In the current study, this relationship between antibiotic resistance genes and virulence factors produced the only statistically significant result, with Shannon diversities of these gene categories being positively correlated (0.553, P = 0.05).…”
Section: Resultsmentioning
confidence: 46%
“…However, whether this enrichment is associated with non-specific intestinal inflammation 17 or the diverticular disease process will require further research. Pseudomonas is an organism which in healthcare settings is known to have a broad range of behavior, but with a potential for antibiotic resistance 18 . Animal models of intestinal anastomoses have shown that Pseudomonas can release collagenases in response to tissue injury 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A network of potential antiquorum sensing agents for P. aeruginosa was created with information from biomedical ontologies and curated databases (MartĂ­n et al, 2017). Some groups have already applied network approaches to study antibiotic resistance in P. aeruginosa, while others have tried to extract information types and apply it to the retrieval and curation of research articles in P. aeruginosa QS (Hwang et al, 2016). In V. fischeri, LuxI is an important component of QS signaling pathway (Engebrecht et al, 1987).…”
Section: Novel Therapeutic Techniques To Target Qsmentioning
confidence: 99%